Superiority of "triple" therapy with salmeterol/fluticasone propionate and tiotropium bromide versus individual components in moderate to severe COPD. Issue 7 (1st February 2008) - Singh, D; Brooks, J; Hagan, G; Cahn, A; O'Connor, B J
Abstract : Background: The combination of salmeterol and fluticasone propionate (SFC) and tiotropium bromide (TIO) are commonly used treatments in chronic obstructive pulmonary disease (COPD) but there are few data on their effectiveness when used together. We compared the effects of SFC 50/500 μg twice daily in addition to TIO 18 μg once daily with the individual treatments alone. Methods: 41 patients with COPD participated in a randomised, double blind, double dummy, three way crossover study with 2 week washout periods between treatments. Lung function assessment included plethysmography and spirometry. The primary end point was post-dose specific airways conductance (sGaw) area under the curve (AUC0–4 h ) on day 14. Results: AUC0–4 h sGaw was significantly higher on day 14 after SFC+TIO compared with TIO (22%) or SFC alone (27%) (both p<0.001). SFC+TIO significantly improved trough forced expiratory volume in 1 s compared with TIO alone (212 ml, p<0.001) and SFC alone (110 ml, p = 0.017) on day 14. Inspiratory capacity measurements also showed significant benefits for triple therapy over individual components on day 14. Subjects receiving SFC+TIO had clinically relevant improvements in Transition Dyspnoea Index (TDI) total score of 2.2 compared with TIO alone (p<0.001) (but not SFC alone, 0.7; NS) and used significantly less rescue medication (1.0 occasion less daily than TIO (p<0.001) and 0.6 less than SFC (p = 0.01)). Conclusion: SFC+TIO triple therapy led to greater improvements in bronchodilation compared with TIO and SFC alone. The advantages of triple therapy are observed across a range of physiologically important parameters, including airway conductance and lung volumes. Triple therapy also led to patient related benefits by improving TDI and use of rescue medication. Trial registration number: NCT00325169.